Festival de música da Paraíba : um estudo sobre as vitrines musicais da rádio tabajara à luz do jornalismo cultural - Venâncio Júnior, Reginaldo (2024)
This research aims to present and describe the creation process of the 1st Paraiba Music Festival, held in 2018, demonstrating how the cultural journalism practiced by Radio Tabajara permeated the process of valuing local culture in the scenario of expanded radio journalism. This is qualitative research, carried out through case studies, documentary research and semi-structured interviews with cultural agents. The research demonstrated stages of creation and development of the Festival, addressing impacts on the artistic career of those who won the first edition, also highlighting initiatives by Radio Tabajara to promote local culture in its programming.